Stuck in the middle: freight forwarder - forwarding agent or contracting carrier? - Rigtering, Mandy Verena (Centre for Law and Society, 2026)
The freight forwarder has always played an important role in commerce and interna tional carriage of goods. Traditionally the freight forwarder was the link between the owner of the goods and the carrier, and provided forwarding or clearing services. The forwarder acted as the agent for the cargo owner, and in some cases at the same time for the carrier. 1 Forwarding agents would have co-operating partners in other countries, to whom they direct instructions for the receipt of the cargo at destination and for cus toms clearance. With the advent of containerisation the forwarder undertook activities such as packing and cargo consolidation on his own account - as principal. In modern days the freight forwarder has adopted a new role in which he is not only assisting the parties in the transportation of goods, but in 'undertaking' the carriage by his own means of transport or by making arrangements with other transport providers. 2 In the role of a principal, the freight forwarder is known by many names, eg Non-Vessel Own ing/ Operating Common Carrier (NVOCC), Multimodal Transport Operator {MTO), lo gistics service provider, etc. 3 In a ·broad sense the activities of a freight forwarder fall under the classical Roman con tract type of mandatum, but nowadays a distinction has to be made between the three different roles a forwarder can fulfil.4 A freight forwarder can act as a mere agent on behalf of his customer or the performing carrier, as the contracting carrier assuming carrier liability without performing the carriage himself or as the performing carrier. 5 The liability of the freight forwarder depends on its role and the governing legal regime.